The relationship between exercise dependence, cognitive style and personality characteristics in candidates participating in physical education and sports school special talent examination - Şenormancı, Güliz; Demir Akca, Ayşe Semra; Şenormancı, Ömer; Akca, Fatih; Gümüş, Mustafa; Köktürk, Fürüzan; Aşkın, Rüstem (The European Research Journal, 2019)
Objectives: It has been suggested that there is a relationship between exercise dependence (ED), perfectionism, self-esteem and some personality characteristics.In the present study, the relations between ED and dysfunctional attitudes, self esteem and personality characteristics were evaluated.Methods: Subjectswere 438 canditates entering special talent examination of Bülent Ecevit University School of Physical Education and Sports, Zonguldak, Turkey. Participants were evaluated with demographic data form prepared by investigators, Exercise Dependence Scale-21 (EDS-21), Dysfunctional Attitude Scale Turkish short form (DAS-R), Eysenk personality quetionnary revised form (EPQR-A) and Rosenberg Self Esteem Scale (RSES).Results: Of the subjects participating in the study, 88 (20.1%) were in dependent (D), 303 (69.2%) in non-dependent-symptomatic (NDS) and 47 (10.7%) in non-dependent-asymptomatic (NDA) groups. There was significant difference in weekly duration of exercise hours between groups (p = 0.003). There was significant difference between groups in terms of DAS-R P/A (Dysfunctional Attitude Scale Turkish short formPerfectionism/achievement) scores. (p = 0.013) In post-hoc Dunn test carried out to determine the significance of the difference in DAS-R P/A scores between groups, no significant difference was found between D and NDS. However, there was significant difference between D and NDA and between NDAand NDS (p < 0.05). In multinomial regression model, it was found that when weekly duration exercise increases 1 unit in the D, 1.082 unit increase occurs compared to NDA (β=1.082, p = 0.012). Conclusions: It was established that in D, perfectionist attitude was seen at a significantly higher rate than non dependent groups and duration of exercise was predictive of ED.